A MOF derived catalyst modified graphite felt electrode with three-dimensional interconnected pore structure and a preparation method thereof

CN123018008APending Publication Date: 2026-10-30ZHEJIANG POLY ENERGY STORAGE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611501474.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]为了克服现有技术中MOF衍生催化剂改性电极存在孔道结构单一的不足,本发明提供了一种具有三维互联孔道结构的MOF衍生催化剂改性石墨毡电极及其制备方法

Benefits of technology

[0022]1.本发明的蛋白质模板具有同时作为成核剂、造孔剂和掺杂源的作用,在MOF生长阶段,蛋白质表面官能团作为成核引导剂,诱导Zn2+和Co2+离子与2-甲基咪唑在蛋白质区域优先配位和成核,避免MOF连续致密包覆导致的传质障碍;在碳化阶段,蛋白质热解作为原位成孔剂,形成介孔-大孔通道,促进电解液快速传输;同时,蛋白质热解产物中的NH3和含氮自由基作为氮源,原位掺杂入双金属MOF衍生碳骨架;氮掺杂提高了催化剂层的催化活性和反应动力学。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018008A_ABST
    Figure CN123018008A_ABST
Patent Text Reader

Abstract

The application discloses a MOF-derived catalyst modified graphite felt electrode with a three-dimensional interconnected pore structure and a preparation method thereof, and steps are as follows: graphite felt pretreatment; protein template self-assembly; protein template guided bimetallic MOF in-situ growth; gradient carbonization to obtain the MOF-derived catalyst modified graphite felt electrode with the three-dimensional interconnected pore structure.The protein template of the application simultaneously serves as a nucleating agent, a pore-forming agent and a doping source, avoids mass transfer obstacles caused by continuous dense coating of MOF, promotes fast transmission of electrolyte, and improves catalytic activity and reaction kinetics of the catalyst layer; and through synergistic distribution of Co and ZnO nanoparticles, catalytic activity of a VO 2+ / VO2 + and V 2+ / V 3+ electricity pair is improved.The application constructs three-stage pores, provides fast permeation channels for electrolyte, promotes ion transmission, and provides rich active sites, and thus improves voltage efficiency, energy efficiency and capacity retention rate of the VRFB.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of vanadium redox flow battery technology, and in particular to a MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected pore structure and its preparation method. Background Technology

[0002] With societal development, green energy sources such as solar, wind, hydro, and bioenergy have been widely developed and utilized. To effectively utilize these energy sources, batteries have been widely applied as an energy storage system. Among various large-scale energy storage systems, vanadium redox flow batteries (VRFBs) have become one of the key technologies in the field of large-scale energy storage due to their high safety, long cycle life, and independently adjustable power / capacity design.

[0003] As the site of vanadium ion redox reactions, the electrode's performance directly determines the battery's energy efficiency, rate performance, and cycle life. Graphite felt, due to its high porosity (≥90%), good conductivity, and chemical stability, is currently the most widely used electrode material in vanadium redox flow batteries (VRFB). However, graphite felt exhibits a tendency to react with vanadium ions... 2+ / VO2 + and V 2+ / V 3+ Inherent defects such as insufficient electrocatalytic activity and poor hydrophilicity of redox pairs limit the performance of batteries at high current densities.

[0004] In recent years, metal-organic framework (MOF)-derived materials have shown great potential in the field of electrocatalysis due to their designable topologies, high specific surface areas, and uniformly dispersed metal active sites. Loading MOF-derived catalysts onto graphite felt surfaces is an effective strategy for improving the electrode performance of vanadium redox flow batteries (VRFB). However, existing MOF-derived catalyst-modified electrodes suffer from problems such as dense catalyst layer structures, high mass transfer resistance, simple pore structures, and insufficient exposure of catalytic active sites. Summary of the Invention

[0005] To overcome the shortcomings of existing MOF-derived catalyst-modified electrodes with a single pore structure, this invention provides a MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected pore structure and its preparation method.

[0006] To achieve the above objectives, the present invention provides a method for preparing a MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected channel structure, characterized by comprising the following steps:

[0007] S1. Heat-treat the graphite felt in hot air;

[0008] S2. Prepare a protein solution containing zein and glutaraldehyde, and adjust the pH of the protein solution to 3-7. Immerse the heat-treated graphite felt in the protein solution, and then vacuum dry it at 60-100℃ to obtain graphite felt loaded with protein template.

[0009] S3. Dissolve zinc salt and cobalt salt in deionized water at a molar ratio of (0.5~3):1, with a total metal ion concentration of 0.01~0.2 mol / L to obtain solution A. Dissolve 2-methylimidazole in deionized water to obtain solution B, wherein the molar ratio of 2-methylimidazole to metal ions is (2~8):1. Slowly add solution B to solution A, stir evenly, and then immerse the graphite felt loaded with protein template. After the reaction is complete, remove it and wash it repeatedly with ethanol and deionized water to remove unreacted metal salts and ligands. After vacuum drying at 60-100℃, obtain graphite felt loaded with MOF / protein template.

[0010] S4. The graphite felt loaded with MOF / protein template is placed in a tube furnace and calcined under an inert atmosphere to obtain a MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected pore structure.

[0011] Preferably, in step S1, the temperature of the hot air is 300~500℃ and the processing time is 1~3h.

[0012] Preferably, in step S2, the concentration of zein is 0.1–5 mg / mL and the concentration of glutaraldehyde is 0.01–0.5 mg / mL.

[0013] Preferably, in step S2, the graphite felt is soaked for 2-4 hours at a temperature of 20-40°C.

[0014] Preferably, in step S3, the zinc salt is one of Zn(NO3)2•6H2O, ZnCl2, or ZnSO4•7H2O.

[0015] Preferably, the cobalt salt is one of Co(NO3)2•6H2O, CoCl2•6H2O or CoSO4•7H2O.

[0016] Preferably, in step S3, the reaction temperature is 20~60℃ and the reaction time is 4~8h.

[0017] Preferably, the calcination in step S4 is gradient calcination, which includes a first stage of gradient calcination. The heating rate of the first stage of gradient calcination is 2~5℃ / min, the calcination temperature is 300~500℃, and the holding time is 1~2h.

[0018] Preferably, the gradient calcination further includes a second gradient calcination stage, wherein the heating rate of the second gradient calcination stage is 5~10℃ / min, the calcination temperature is 700~900℃, and the holding time is 2~4h.

[0019] The present invention also discloses a MOF-derived catalyst modified graphite felt electrode with a three-dimensional interconnected channel structure, wherein the MOF-derived catalyst modified graphite felt is prepared by the above-mentioned method for preparing a MOF-derived catalyst modified graphite felt electrode with a three-dimensional interconnected channel structure.

[0020] By adopting the above scheme, this invention constructs a MOF-derived catalytic layer with three-dimensional interconnected channels on the surface of graphite felt carbon fiber through an innovative technical route of "pre-implanted protein template - template-induced MOF localization growth and template-assisted pore formation - gradient calcination". This can not only give full play to the high catalytic activity of MOF-derived catalyst, but also avoid the mass transfer barrier problem caused by dense coating. This is of great significance for promoting the large-scale application of all vanadium redox flow batteries.

[0021] The present invention also has the following beneficial effects:

[0022] 1. The protein template of the present invention simultaneously functions as a nucleating agent, a pore-forming agent, and a dopant source. During the MOF growth stage, the protein surface functional groups act as nucleation guides, inducing Zn... 2+ and Co 2+ Ions preferentially coordinate and nucleate with 2-methylimidazole in the protein region, avoiding mass transfer barriers caused by continuous dense MOF coating; during the carbonization stage, protein pyrolysis acts as an in-situ pore-forming agent, forming mesoporous-macroporous channels to promote rapid electrolyte transport; at the same time, NH3 and nitrogen-containing free radicals in the protein pyrolysis products serve as nitrogen sources, in-situ doping into the bimetallic MOF-derived carbon framework; nitrogen doping improves the catalytic activity and reaction kinetics of the catalyst layer.

[0023] 2. This invention utilizes Zn 2+ and Co 2+ Co-coordination forms a bimetallic MOF precursor, achieving a synergistic distribution of Co and ZnO nanoparticles after carbonization; Co and ZnO nanoparticles act as highly efficient catalysts for the redox reaction of vanadium ions, promoting the oxidation-reduction reaction of vanadium ions. 2+ / VO2 + and V 2+ / V 3+ Both redox couples exhibit good catalytic activity.

[0024] 3. The bimetallic MOF-derived catalytic layer of the present invention comprises interconnected tertiary channels: primary mesoporous-macroporous channels originate from the pyrolysis of protein templates, providing rapid permeation channels for electrolytes; secondary mesoporous-mesoporous channels originate from the dispersion of Co / ZnO nanoparticles in the carbon skeleton, promoting ion transport; and tertiary microporous-mesoporous channels originate from the carbonization of MOF organic ligands, providing abundant active sites.

[0025] In summary, this invention constructs a three-dimensional continuous pore system inside the catalytic layer by creating pores in situ using protein templates, which effectively reduces concentration polarization and enables the electrode to maintain high efficiency operation even under high current density.

[0026] The present invention will now be further described with reference to the accompanying drawings. Attached Figure Description

[0027] Appendix Figure 1 This is a pore size distribution diagram of Embodiment 1 and Comparative Example 1 of the present invention. Detailed Implementation

[0028] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. In addition, in the following description, descriptions of well-known structures and technologies are omitted to avoid unnecessarily obscuring the concept of the present invention.

[0029] The specific embodiments of the present invention illustrate a method for preparing a MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected channel structure.

[0030] Includes the following steps:

[0031] S1. Pretreatment of graphite felt: Treat the graphite felt in hot air at 300~500℃ for 1~3 hours to increase the hydrophilicity and oxygen-containing functional group density on the surface of the graphite felt.

[0032] S2. Protein template self-assembly: The heat-treated graphite felt is immersed in a solution containing 0.1-5 mg / mL zein and 0.01-0.5 mg / mL glutaraldehyde, the pH is adjusted to 3-7, and the solution is soaked at 20-40℃ for 2-4 hours. Then, it is vacuum dried at 60-100℃ to obtain graphite felt loaded with protein templates. Preferably, the solution is vacuum dried at 80℃.

[0033] S3. Protein template-induced in situ growth of MOFs: Zinc and cobalt salts are dissolved in deionized water at a molar ratio of (0.5~3):1, with a total metal ion concentration of 0.01~0.2 mol / L, to obtain solution A. 2-Methylimidazole is dissolved in deionized water at a molar ratio of 2-methylimidazole to metal ions of (2~8):1, to obtain solution B. Solution B is slowly added to solution A, stirred evenly, and then immersed in a graphite mat loaded with a protein template. After reacting at 20~60℃ for 4~8 h, the graphite mat is removed, repeatedly washed with ethanol and deionized water to remove unreacted metal salts and ligands, and then vacuum dried at 60-100℃ to obtain a graphite mat loaded with a MOF / protein template, preferably vacuum dried at 80℃. The zinc salt is one of Zn(NO3)2•6H2O, ZnCl2 or ZnSO4•7H2O, and the cobalt salt is one of Co(NO3)2•6H2O, CoCl2•6H2O or CoSO4•7H2O.

[0034] S4. Carbonization treatment: The graphite felt loaded with MOF / protein template is placed in a tube furnace and subjected to gradient calcination under an inert atmosphere. The gradient combustion includes a first stage and a second stage. First, the graphite felt is heated to 300-500℃ at a rate of 2-5℃ / min and calcined for 1-2 hours. Then, the graphite felt is heated to 700-900℃ at a rate of 5-10℃ / min and calcined for 2-4 hours. After calcination, the MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected pore structure is obtained.

[0035] The protein template of this invention simultaneously serves as a nucleating agent, pore-forming agent, and dopant source. During the MOF growth stage, the protein surface functional groups act as nucleation guides, inducing preferential coordination and nucleation of the MOF within the protein region, avoiding mass transfer barriers caused by continuous dense MOF coating. During the carbonization stage, the protein acts as an in-situ pore-forming agent, forming mesoporous-macroporous channels to promote rapid electrolyte transport. Simultaneously, NH3 and nitrogen-containing free radicals from the protein pyrolysis products serve as nitrogen sources, in-situ doping into the bimetallic MOF-derived carbon framework. Nitrogen doping enhances the catalytic activity and reaction kinetics of the catalyst layer. Furthermore, Zn... 2+ and Co 2+ Co-coordination forms a bimetallic MOF, which, after carbonization, achieves a synergistic distribution of Co and ZnO nanoparticles, thus enhancing the performance of VO2max. 2+ / VO2 + and V 2+ / V 3+ Both redox couples exhibit excellent catalytic activity. The bimetallic MOF-derived catalyst layer prepared in this invention comprises interconnected tertiary channels, providing rapid permeation channels for the electrolyte, promoting ion transport, and offering abundant active sites, thereby improving the voltage efficiency, energy efficiency, and capacity retention of VRFB.

[0036] Example 1:

[0037] This embodiment is obtained through the following operations:

[0038] S1. Treat the graphite felt in hot air at 300℃ for 1 hour to increase the hydrophilicity and oxygen-containing functional group density on the surface of the graphite felt.

[0039] S2. The heat-treated graphite felt was immersed in a solution containing 0.1 mg / mL zein and 0.01 mg / mL glutaraldehyde, and the pH was adjusted to 3. After soaking at 20°C for 2 hours, it was vacuum dried at 80°C to obtain graphite felt loaded with protein templates.

[0040] S3. Dissolve zinc salt and cobalt salt in deionized water at a molar ratio of 0.5:1, resulting in a total metal ion concentration of 0.01 mol / L, to obtain solution A. Dissolve 2-methylimidazole in deionized water at a molar ratio of 2-methylimidazole to metal ions of 2:1, to obtain solution B. Slowly add solution B to solution A, stir well, and then immerse the protein template-loaded graphite felt in the solution. After reacting at 20℃ for 4-8 hours, remove the graphite felt, repeatedly wash it with ethanol and deionized water to remove unreacted metal salts and ligands, and vacuum dry it at 80℃ to obtain the MOF / protein template-loaded graphite felt.

[0041] S4. The graphite felt loaded with MOF / protein templates was placed in a tube furnace and subjected to gradient calcination under an inert atmosphere. First, in the first stage of gradient calcination, the temperature was increased to 300℃ at a rate of 2℃ / min and calcined for 1 h. Then, in the second stage of gradient calcination, the temperature was increased to 700℃ at a rate of 5℃ / min and calcined for 2 h, yielding a MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected porous structure.

[0042] Example 2:

[0043] S1. Treat the graphite felt in hot air at 400℃ for 2 hours to increase the hydrophilicity and oxygen-containing functional group density on the surface of the graphite felt.

[0044] S2. The heat-treated graphite felt was immersed in a solution containing 2 mg / mL zein and 0.2 mg / mL glutaraldehyde, and the pH was adjusted to 5. After soaking at 30°C for 3 hours, it was vacuum dried at 80°C to obtain graphite felt loaded with protein templates.

[0045] S3. Dissolve zinc salt and cobalt salt in deionized water at a molar ratio of 2:1, resulting in a total metal ion concentration of 0.1 mol / L, to obtain solution A. Dissolve 2-methylimidazole in deionized water at a molar ratio of 5:1 to metal ions, to obtain solution B. Slowly add solution B to solution A, stir well, and then immerse the protein template-loaded graphite felt in the solution. After reacting at 40°C for 6 hours, remove the graphite felt, repeatedly wash it with ethanol and deionized water to remove unreacted metal salts and ligands, and vacuum dry it at 80°C to obtain MOF / template-loaded graphite felt.

[0046] S4. The graphite felt loaded with MOF / protein templates was placed in a tube furnace and subjected to gradient calcination under an inert atmosphere. First, in the first stage of gradient calcination, the temperature was increased to 400℃ at a rate of 3℃ / min and calcined for 1.5 h. Then, in the second stage of gradient calcination, the temperature was increased to 800℃ at a rate of 7℃ / min and calcined for 3 h. After calcination, a MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected porous structure was obtained.

[0047] Example 3:

[0048] S1. Treat the graphite felt in hot air at 500℃ for 3 hours to increase the hydrophilicity and oxygen-containing functional group density on the surface of the graphite felt.

[0049] S2. The heat-treated graphite felt was immersed in a solution containing 5 mg / mL zein and 0.5 mg / mL glutaraldehyde, and the pH was adjusted to 7. After soaking at 40°C for 4 hours, it was vacuum dried at 80°C to obtain graphite felt loaded with protein templates.

[0050] S3. Dissolve zinc salt and cobalt salt in deionized water at a molar ratio of 3:1, resulting in a total metal ion concentration of 0.2 mol / L, to obtain solution A. Dissolve 2-methylimidazole in deionized water at a molar ratio of 2-methylimidazole to metal ions of 8:1, to obtain solution B. Slowly add solution B to solution A, stir well, and then immerse the protein template-loaded graphite felt in the solution. After reacting at 60°C for 8 hours, remove the graphite felt, repeatedly wash it with ethanol and deionized water to remove unreacted metal salts and ligands, and then vacuum dry it at 80°C to obtain MOF / template-loaded graphite felt.

[0051] S4. The MOF / template-loaded graphite felt was placed in a tube furnace and subjected to gradient calcination under an inert atmosphere. First, in the first stage of gradient calcination, the temperature was increased to 500℃ at a rate of 5℃ / min and calcined for 2 hours. Subsequently, in the second stage of gradient calcination, the temperature was increased to 900℃ at a rate of 10℃ / min and calcined for 4 hours. After calcination, a MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected pore structure was obtained.

[0052] Comparative Example 1:

[0053] This comparative example is a blank control group, that is, using untreated blank carbon cloth.

[0054] Comparative Example 2:

[0055] The preparation process of this comparative example differs from that of Example 1 in that step S2 is omitted.

[0056] Comparative Example 3:

[0057] The preparation process of this comparative example differs from that of Example 1 only in that step S3 is omitted.

[0058] The electrodes prepared in Examples 1-3 and Comparative Examples 1-3 were respectively assembled into battery stacks and subjected to charge-discharge tests under the same test conditions. The coulombic efficiency, voltage efficiency, energy efficiency, and capacity retention after 100 cycles were recorded. The test results are shown in Table 1.

[0059] Table 1. Performance test results of graphite felt in the examples and comparative examples

[0060]

[0061] As shown in Table 1, compared with Comparative Example 1, Examples 1-3 exhibit higher voltage efficiency, energy efficiency, and capacity retention. This is mainly because Examples 1-3 prepared MOF-derived catalyst-modified graphite felt electrodes with a three-dimensional interconnected porous structure. The use of natural protein templates enabled the spatially selective distribution and functional integration of the catalyst layer on the carbon fiber surface, solving problems such as dense catalyst layers, high mass transfer resistance, weak interfacial bonding, and limited single-metal catalytic activity in conventional MOF-modified electrodes. Compared with Comparative Example 2, Examples 1-3 exhibited higher voltage efficiency, energy efficiency, and capacity retention, primarily because the protein templates acted not only as nucleating agents but also as pore-forming agents and dopant sources. During the MOF growth stage, the surface functional groups of the protein served as nucleation guides, inducing Zn... 2+ and Co 2+ Ions preferentially coordinate and nucleate with 2-methylimidazole in protein regions, achieving spatially selective distribution; during the carbonization stage, protein pyrolysis acts as an in-situ pore-forming agent, forming mesoporous-macroporous channels and promoting rapid electrolyte transport. For example... Figure 1 As shown, Example 1 exhibits more mesopores and macropores, demonstrating that the protein template, acting as a pore-forming agent, forms mesopores and macropores after pyrolysis. Simultaneously, NH3 and nitrogen-containing free radicals from the protein pyrolysis products serve as nitrogen sources, in-situ doping into the bimetallic MOF-derived carbon framework. Nitrogen doping enhances the catalytic activity and reaction kinetics of the catalyst layer. Compared to Comparative Example 3, Examples 1-3 demonstrate higher voltage efficiency, energy efficiency, and capacity retention, primarily because Examples 1-3 utilize Zn... 2+ and Co 2+Co-coordination forms a bimetallic MOF precursor, achieving a synergistic distribution of Co and ZnO nanoparticles after carbonization. Co and ZnO nanoparticles act as highly efficient catalysts for the redox reaction of vanadium ions, promoting the efficient distribution of vanadium ions. 2 + / VO2 + and V 2+ / V 3+ Both redox couples exhibit good catalytic activity.

[0062] This invention is not limited to the specific embodiments described above. The technical features of the above embodiments can be combined arbitrarily. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as the combination of these technical features does not contradict each other, it should be considered within the scope of this specification. Those skilled in the art can implement this invention using various other specific embodiments based on the content disclosed herein. Any modifications or alterations made to the design structure and concept of this invention fall within the protection scope of this invention.

Claims

1. A method for preparing a MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected channel structure, characterized in that, Includes the following steps: S1. Heat-treat the graphite felt in hot air; S2. Prepare a protein solution containing zein and glutaraldehyde, and adjust the pH of the protein solution to 3-7. Immerse the heat-treated graphite felt in the protein solution, and then vacuum dry it at 60-100℃ to obtain graphite felt loaded with protein template. S3. Dissolve zinc salt and cobalt salt in deionized water at a molar ratio of (0.5~3):1, with a total metal ion concentration of 0.01~0.2 mol / L to obtain solution A. Dissolve 2-methylimidazole in deionized water to obtain solution B, wherein the molar ratio of 2-methylimidazole to metal ions is (2~8):

1. Slowly add solution B to solution A, stir evenly, and then immerse the graphite felt loaded with protein template. After the reaction is complete, remove it and wash it repeatedly with ethanol and deionized water to remove unreacted metal salts and ligands. After vacuum drying at 60-100℃, obtain graphite felt loaded with MOF / protein template. S4. The graphite felt loaded with MOF / protein templates is placed in a tube furnace and calcined under an inert atmosphere to obtain a MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected pore structure.

2. The method for preparing a MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected channel structure as described in claim 1, characterized in that: In step S1, the temperature of the hot air is 300~500℃, and the processing time is 1~3h.

3. The method for preparing a MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected channel structure as described in claim 1, characterized in that: In step S2, the concentration of zein is 0.1–5 mg / mL, and the concentration of glutaraldehyde is 0.01–0.5 mg / mL.

4. The method for preparing a MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected channel structure as described in claim 1, characterized in that: In step S2, the graphite felt is soaked for 2-4 hours at a temperature of 20-40°C.

5. The method for preparing a MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected channel structure as described in claim 1, characterized in that: In step S3, the zinc salt is one of Zn(NO3)2•6H2O, ZnCl2, or ZnSO4•7H2O.

6. The method for preparing a MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected channel structure as described in claim 1, characterized in that: The cobalt salt is one of Co(NO3)2•6H2O, CoCl2•6H2O or CoSO4•7H2O.

7. The method for preparing a MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected channel structure as described in claim 1, characterized in that: In step S3, the reaction temperature is 20~60℃ and the reaction time is 4~8h.

8. The method for preparing a MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected channel structure as described in claim 1, characterized in that: The calcination in step S4 is gradient calcination, which includes a first stage of gradient calcination. The heating rate of the first stage of gradient calcination is 2~5℃ / min, the calcination temperature is 300~500℃, and the holding time is 1~2h.

9. The method for preparing a MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected channel structure as described in claim 8, characterized in that: The gradient calcination also includes a second gradient calcination stage, wherein the heating rate of the second gradient calcination stage is 5~10℃ / min, the calcination temperature is 700~900℃, and the holding time is 2~4h.

10. A MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected pore structure, characterized in that, The MOF-derived catalyst-modified graphite felt is prepared using the method described in any one of claims 1-9 for preparing a MOF-derived catalyst-modified graphite felt electrode with a three-dimensional interconnected pore structure.